2016
DOI: 10.1016/j.ultras.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on effects of frequency in ultrasonically-assisted end-milling of AISI 316L: A feasibility study

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Tsai et al [84] investigated the machining of hard mold steel by ultrasonic assisted end milling, and found that a positive rake angle and a large helix angle gave improved surface finish. Maurotto and Wickramarachchi [85] investigated the effects of frequency in ultrasonically assisted end milling on grain sizes of AISI 316L. They found that grain sizes appeared comparable with conventional milling and there was no sign of grain rotations, grain refinements, or strongly deformed areas indicative of significant machining abuse, as shown in Fig.…”
Section: End Millingmentioning
confidence: 99%
“…Tsai et al [84] investigated the machining of hard mold steel by ultrasonic assisted end milling, and found that a positive rake angle and a large helix angle gave improved surface finish. Maurotto and Wickramarachchi [85] investigated the effects of frequency in ultrasonically assisted end milling on grain sizes of AISI 316L. They found that grain sizes appeared comparable with conventional milling and there was no sign of grain rotations, grain refinements, or strongly deformed areas indicative of significant machining abuse, as shown in Fig.…”
Section: End Millingmentioning
confidence: 99%
“…This is because the ratio of the vibration frequency f to spindle speed n decreased as cutting speeds went up. It means that the tool-workpiece contact ratio (TWCR) escalates as cutting speeds increase and the engagement time between the tool and the workpiece in single vibration cycle lasts longer at higher cutting speeds [19]. The excellent cooling and lubrication effects brought by separation characteristic in HRUEM will be weakened at a higher value of TWCR and more heat accumulates in the cutting zone.…”
Section: Tool Lifementioning
confidence: 99%
“…As an intermittent cutting method, ultrasonic vibration machining (UAM) has been widely discussed for its ability to open the tool-workpiece contact area intermittently. As one of the typical UAM processes, the ultrasonic-assisted milling technique has been widely applied to machine difficult-to-cut alloys for its superiority in expanding tool life, lowering cutting force and delivering better surface quality [18][19][20][21][22][23][24]. In order to obtain the intermittent cutting mode between the tool and the workpiece in UAM, its relative velocity in cutting direction should be controlled as the opposite to the tool rotation direction periodically.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the low thermal conductivity of titanium alloy lead to high temperature near cutting point, and under UVAM condition, the periodic separation between tool and workpiece can be beneficial to the heat dissipation. [17][18][19] Figure 10 gives the surface roughness of the slot bottom of 6061T6 and TC4 with different feed rates under CM and UVAM condition. Figures 11-13 are slot bottom images for 6061T6 and Figures 14-16 for TC4 under different milling conditions.…”
Section: Milling Forcementioning
confidence: 99%